The Effectiveness of Story-Based Learning in Enhancing Speaking Confidence of Fifth-Grade Students in Elementary Schools: A Literature Review - Tiarnita Maria Sarjani; Farah Nabila; Eunike Gracia Sormin; Monica Intan Reni (IJESS International Journal of Education and Social Science, 2026)
This study aims to examine the effectiveness of story-based learning in enhancing the speaking confidence of fifth-grade elementary school students through a literature review. The main research question addressed is how story-based learning influences students’ speaking confidence and what strategies contribute to its success. This study employed a qualitative literature review method by analyzing relevant empirical studies on storytelling, paired storytelling, hand puppets, digital storytelling, and public speaking classes. The findings consistently indicate significant improvements in students’ speaking skills and self-confidence, as evidenced by increased post-test scores, strong statistical significance (p < 0.05), and positive behavioral changes such as greater courage, fluency, and expressiveness. The review concludes that story-based learning is an effective and comprehensive pedagogical strategy for fostering speaking confidence and active classroom participation among fifth-grade students.